Sesquiterpenoids and monoterpenoids from the water decoction of Valeriana officinalis L. (January 2023) - Li, Shi-Wei; Xue, Bian-Xia; Yang, Tian-Tian; Li, Ran; Zhang, Mingjie; Wang, Miao; Zhang, Li-Hua; Zhang, Peng; Zhang, Yi; Wang, Tao; Wang, Shao-Xia; Wu, Hong-Hua
Abstract: Nine previously undescribed compounds including three sesquiterpenoids, three iridoids, two monoterpenoids and a furan fatty acid, along with seventeen known ones, were isolated from the water decoction of roots and rhizomes of Valeriana officinalis L. Structure elucidation of the twenty-six compounds were accomplished by analysis of the extensive spectroscopic data, and the absolute configurations of the nine previously undescribed ones were established by NOESY experiment and the electronic circular dichroism (ECD) simulations. Among them, β- patchoulene-8- O-β- D-glucopyranoside, 11-methoxyl-viburtinal, and protocatechuic acid showed anti-neuroinflammatory potentials by significantly inhibiting the secretion of nitric oxide (NO) on BV-2 cells upon LPS stimulation ( p  < 0.001) without affecting the cell viability. Graphical abstract: Nine previously undescribed compounds, along with seventeen known ones, were isolated from the water decoction of roots and rhizomes of Valeriana officinalis L., and their anti-neuroinflammatory properties were evaluated by inhibiting nitric oxide (NO) secretion on BV-2 cells upon LPS stimulation. Image 1 Highlights: Twenty-six compounds were isolated from the water decoction of Valeriana officinalis. Nine previously undescribed compounds were reported from Valeriana officinalis. Three compounds with anti-neuroinflammatory potentials were reported.